1995
DOI: 10.1016/0378-4290(94)00095-t
|View full text |Cite
|
Sign up to set email alerts
|

Wind erosion control using crop residue II. Effects on millet establishment and yields

Abstract: Effects of three levels of millet stover residue (0, 500, and 2000 kg ha-') on establishment and growth of pearl millet (Pennisetum glaucum (L.) R.Br) were determined in a wind-erosion-affected area in Niger, West Africa, during 1991 and 1992. The extent of millet seedlings buried by blown soil in plots with 500 kg ha-' residues was similar to that of control plots. A residue amount of 2000 kg ha-' reduced the extent of covered millet, but did not provide complete protection during severe sand storms. Partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…And for pattern P.D, while in run 2 the pattern and % cover were sufficient to reach an equilibrium between erosion and deposition, in run 3 (higher average wind speed) more erosion occurred. Several previous studies have indicated that limited surface cover (5-7.5%) combined with a certain minimum wind speed can increase windblown mass fluxes (Raupach, 1990;Raupach, 1992;Raupach et al, 1993;Michels et al, 1995;Sterk et al, 1998;Maurer et al, 2009) due to the increased turbulence caused by the limited vegetation cover. The effect of the wind speed on the increased mass flux is illustrated in the difference between runs 2 and 3 for pattern P.D.…”
Section: Sediment Transport Between Bare and Vegetated Land Unitsmentioning
confidence: 99%
“…And for pattern P.D, while in run 2 the pattern and % cover were sufficient to reach an equilibrium between erosion and deposition, in run 3 (higher average wind speed) more erosion occurred. Several previous studies have indicated that limited surface cover (5-7.5%) combined with a certain minimum wind speed can increase windblown mass fluxes (Raupach, 1990;Raupach, 1992;Raupach et al, 1993;Michels et al, 1995;Sterk et al, 1998;Maurer et al, 2009) due to the increased turbulence caused by the limited vegetation cover. The effect of the wind speed on the increased mass flux is illustrated in the difference between runs 2 and 3 for pattern P.D.…”
Section: Sediment Transport Between Bare and Vegetated Land Unitsmentioning
confidence: 99%
“…It could cause much damage such as crop decrease, soil fertility reduction, dust storms and land degradation [3][4][5]. Many methods, including planting trees, erecting hedges and mulching crop residue, have been carried out to reduce the damage [6,7]. However, these methods have some problems such as being time and labor consuming, with low effectiveness and high cost.…”
Section: Introductionmentioning
confidence: 98%
“…The 40 mainplot treatments attributed to plots of 10 by 10 m the pipette method (Gee and Bauder, 1986).…”
Section: Methodsmentioning
confidence: 99%